Farmers in Vihiga transform their food system through multi-sectoral and multi-actor approaches - Termote, Celine; Jordan, Irmgard; Oduor, Francis; Akingbemisilu, Tosin; Tosin Harold Akingbemisilu: 0000-0002-0556-9955 (2024)
Integrated community-basedapproachfor farm, marketand dietdiversity, hadsignificantpositive effectson women’sand children’sdietarydiversityin 2 rounds (2015-2016 / 2018 –2020)